2017
DOI: 10.1002/2016ef000503
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐model and multi‐scenario assessments of Asian water futures: The Water Futures and Solutions (WFaS) initiative

Abstract: This paper presents one of the first quantitative scenario assessments for future water supply and demand in Asia to 2050. The assessment, developed by the Water Futures and Solutions (WFaS) initiative, uses the latest set of global climate change and socioeconomic scenarios and state-of-the-art global hydrological models. In Asia, water demand for irrigation, industry, and households is projected to increase substantially in the coming decades (30-40% by 2050 compared to 2010). These changes are expected to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 59 publications
1
35
0
2
Order By: Relevance
“…Risks are not just dependent on the severity of climate change and subsequent hazards but critically depend on the population's spatial distribution (exposure) and their vulnerability and capacity to prepare for and manage changing risks [5]. Increasingly studies are showing that the world's poorest are disproportionately exposed to changes in temperature extremes [6,7] and challenging hydro-climatic complexity [8][9][10]. In the water sector, between 8%-14% of the global population are expected to face severe reductions in available water resources between 1.7 • C-2.7 • C [11] and in the energy sector, more than 70% of a 'business as usual' 2050s population could expect climate sensitive changes in energy demand of +/− 5%, with negative impacts overwhelmingly in low and middle income countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…Risks are not just dependent on the severity of climate change and subsequent hazards but critically depend on the population's spatial distribution (exposure) and their vulnerability and capacity to prepare for and manage changing risks [5]. Increasingly studies are showing that the world's poorest are disproportionately exposed to changes in temperature extremes [6,7] and challenging hydro-climatic complexity [8][9][10]. In the water sector, between 8%-14% of the global population are expected to face severe reductions in available water resources between 1.7 • C-2.7 • C [11] and in the energy sector, more than 70% of a 'business as usual' 2050s population could expect climate sensitive changes in energy demand of +/− 5%, with negative impacts overwhelmingly in low and middle income countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of three different models showed for SSP2 a range of 25–125% increase, with an average of 85% (Wada et al, ), showing that our results are within this range—although on the low side (in an earlier paper, we discussed that the main reason is that we assume a higher efficiency increase; Bijl et al, ). Regional patterns across the models are comparable showing most increase in Africa and Asia (Satoh et al, ; Wada et al, ). In the WaterEff scenario, the socioeconomic drivers from SSP‐2 combined with the efficiencies of SSP‐1 result in a nonagricultural demand increase of 37% during 2010–2050.…”
Section: Discussionmentioning
confidence: 91%
“…Hanasaki et al () developed a set of integrative scenarios of water use for all sectors based on the Shared Socioeconomic Pathways (SSPs; O'Neill et al, ) and demonstrated that the socioeconomic scenarios and associated water use scenario dominate the impact of the water scarcity in the 21st century. Since then, different integrated model‐based scenarios have been developed to understand the global water use and demand (Parkinson et al, ; Satoh et al, ; Wada et al, ), mostly using the SSP scenarios as their basis focusing on industrial use or, for instance, on coupled climate development impacts (Parkinson et al, ). These studies conclude that socioeconomic changes are the main drivers of water scarcity, for all SSP scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Continued depletion of finite groundwater reserves raises globally significant threats, including abrupt agricultural decline (Aeschbach-Hertig & Gleeson, 2012) and associated disruption to internationally traded food supplies (Dalin et al, 2017). The problem is likely to worsen as socioeconomic development increases global demands for water (Satoh et al, 2017). Sustainable management of groundwater is thus marked as a major global policy challenge, requiring risk analysis informed by long-range projections of aquifer exploitation and exhaustion across the world's most important basins of irrigated agriculture (Ashraf et al, 2017;Connor, 2015).…”
Section: Introductionmentioning
confidence: 99%